Long-Term Outcomes of Pediatric Renovascular Hypertension - Hyun Chung; Jae Hwan Lee; Eujin Park; Hyesun Hyun; Yo Han Ahn; Hwan Jun Jae; Gi Beom Kim; Il Soo Ha; Hae Il Cheong; Hee Gyung Kang (Karger Publishers, 2017)
Background/Aims: Renovascular hypertension (RVHT) is an important cause of childhood hypertension. This study evaluated the clinical characteristics and outcomes of Korean children with RVHT. Methods: Children treated for RVHT between 2000 and 2015 at our center were retrospectively reviewed. Results: Forty-six children were followed for a median of 6.5 (0.66-27.23) years. Forty-five percutaneous transluminal angioplasties (PTAs) were performed in 32 children. At the last visit, clinical benefit was observed in 53.3% of children. Patients with comorbid cerebrovascular disease (CVD) showed less favorable long-term outcomes after PTA (clinical benefit in 41.7% vs. 61.1% in others) and higher restenosis rates (50% vs. 31.6% in others). Surgical procedures (bypass or nephrectomy) were performed in 8 patients. After surgery, blood pressure was normalized in 2 patients, improved in 3 patients, and unchanged in the remaining patients. Between PTA group (n=21) and medication group (n=14), percentage of atrophic kidneys became higher after follow-up period in medication group than in PTA group (60.0% vs. 26.1%, P=0.037). Conclusion: Aggressive treatment of pediatric RVHT yielded fair outcomes in our cohort. CVD comorbidity was associated with relatively poor PTA outcomes. To confirm our findings, larger cohort studies with a longer follow-up period are warranted.